Revised taxonomic classification of the Stenotrophomonas genomes, providing new insights into the genus Stenotrophomonas - Yu, Ze-Lin; Wang, Rui-Bai (Frontiers in Microbiology, 2024)
BackgroundStenotrophomonas strains are important opportunistic pathogens with great potential applications in industry and agriculture. Their significant genetic and phenotypic diversity has led to several changes in their taxonomic localization and was prone to inaccurate species classification based on traditional identification methods.MethodsAll 2,615 genomes of the genus Stenotrophomonas were obtained from the NCBI genome database. Genomic methods, including average nucleotide identity (ANI), were used to evaluate the 31 defined species. After evaluating the ANI thresholds applicable to Stenotrophomonas, the species classification of all submitted genomes was revised.ResultsCompared to the reference genomes of each species, 41.17% of the submitted Stenotrophomonas genomes had ANI values below 95, and 8.58% of the genomes were even below 90%. Moreover, 45.3% (705/1555) of the S. maltophilia strains actually belonged to other species within the S. maltophilia complex (Smc), or even to distant relatives outside the Smc. Based on the ANI threshold values of 95 and 90% for species and complexes confirmed to be applicable to Stenotrophomonas, 2,213 submitted Stenotrophomonas genomes were re-divided into 116 ANI genome species.ConclusionThe results confirmed that 16S rRNA gene sequencing has low discriminability for the closely related Stenotrophomonas species. The annotated species of a considerable strain were indeed incorrect, especially since many S. maltophilia strains did not belong to this representative pathogenic species of Stenotrophomonas. This makes it necessary to reconsider the evolutionary relationship, pathogenicity, and clinical significance of Stenotrophomonas.